The Implementation of Flashcard Game on Vocabulary Mastery - Dinar Vincy Yunitaka Bahrudin (Wacana Didaktika, 2015)
Learning vocabulary is difficult for some students. There are a number of factors causing the difficulty of learning vocabulary: first is from students‟ point of view who argued that a lot of various different vocabularies should be learned by the students in a short time in which they memorize them but often forget. Second is from teacher‟s point of view who said that teachers‟ technique (traditional memorization) and media (power point) in teaching vocabulary were almost never changed for a long time. Therefore this study is aimed at investigating the effectiveness of teaching vocabulary using flashcard game on vocabulary mastery.